From the Wild to the Cup: Tracking Footprints of the Tea Species in Time and Space - Wambulwa, Moses C.; Meegahakumbura, Muditha K.; Kamunya, Samson; Wachira, Francis N. (Frontiers in Nutrition, 2021)
Tea is one of the world’s most popular beverages, known for its cultural significance and numerous health benefits. A clear understanding of the origin and history of domestication of the tea species is a fundamental pre-requisite for effective germplasm conservation and improvement. Though there is a general consensus about the center of origin of the tea, the evolutionary origin and expansion history of the species remain shrouded in controversy, with studies often reporting conflicting findings. This mini review provides a concise summary of the current state of knowledge regarding the origin, domestication, and dissemination of the species around the world. Markedly, we note that tea was domesticated around 3000 B.C. either extra-specifically from non-tea wild relatives (probably Camellia grandibracteata and/or C. leptophylla) or intra-specifically from the wild Camellia sinensis var assamica trees, and that the genetic origins of the various tea varieties may need further inquiry. Moreover, lineage divergence within the tea family seems to have been driven largely by a combination of orogenic, climatic, and human-related forces, a fact that could have far-reaching implications for the conservation of the contemporary tea germplasm. Finally, we demonstrate the robustness of an integrative approach involving linguistics, historical records, and genetics to identify the center of origin of the tea species and its history of expansion. Throughout the review, we identify areas of debate, and highlight potential research gaps, which would form the basis for future explorations of the topic.